Neurohybrid Memristive CMOS-Integrated Systems for Biosensors and Neuroprosthetics - Mikhaylov, Alexey; Pimashkin, Alexey; Pigareva, Yana; Gerasimova, Svetlana; Gryaznov, Evgeny; Shchanikov, Sergey; Zuev, Anton; Talanov, Max; Lavrov, Igor; Demin, Vyacheslav; Erokhin, Victor; Lobov, Sergey; et al. (Frontiers in Neuroscience, 2020)
Here we provide a perspective concept of neurohybrid memristive chip based on the combination of living neural networks cultivated in microfluidic / microelectrode system, metal-oxide memristive devices or arrays integrated with mixed-signal CMOS layer to control the analog memristive circuits, process the decoded information and arrange a feedback stimulation of biological culture as parts of a bidirectional neurointerface. Our main focus is on the state-of-the-art approaches for cultivation and spatial ordering of the network of dissociated hippocampal neuron cells, fabrication of a large-scale cross-bar array of memristive devices tailored using device engineering, resistive state programming or nonlinear dynamics, as well as hardware implementation of spiking neural networks based on the arrays of memristive devices and integrated CMOS electronics. The concept represents an example of a brain-on-chip system belonging to a more general class of memristive neurohybrid systems for a new-generation robotics, artificial intelligence, and personalized medicine, discussed in the framework of the proposed roadmap for the next decade period.